Efektivitas Pelatihan Asertif Sebagai Upaya Mengatasi Perilaku “Bullying” di SMPN A Surabaya - Hilda Rosa Ainiyah; Ika Yuniar Cahyanti (Psikostudia : Jurnal Psikologi, 2020)
Bullying is one of the serious problems that is vulnerable to occur in adolescence as experienced by students of  9th grade SMPN A Surabaya. Bullying has a variety of negative impacts on victims and people who witness or bystander that see bullying behavior, that is including physical and psychological impacts. Bullying can be overcome by assertive behavior. Assertive behavior makes the victim and bystander able to express opinions straightforwardly and boldly without hurting the offender to stop bullying behavior. Assertive behavior can be enhanced through assertive training. This research was conducted with the aim of seeing the effectiveness of assertive training to: (1) increase students' understanding of bullying and assertive behavior; and (2) increasing assertive behavior of students to be able to overcome bullying at schools. This research is a quantitative research with experimental method. The type of experiments conducted are one group pretest-posttest design. Subjects are selected by purposive sampling. The subjects involved were 25 students in 9th grade students of SMPN A Surabaya. Assertive behavior is measured by the assertiveness scale by Robert E. Alberti and Michael L. Emmons (2002) which has been translated into Indonesian by Nabila (2015). Assertiveness scale is given before and after training for each subject. Subjects underwent 8 training sessions which were held for 2 days. The collected data was analyzed by paired sample t-test. The results show that: (1) there are significant differences in the subject's understanding of bullying and assertiveness before and after the study, where the subject's average understanding increases after training; (2) student assertiveness behavior significantly increases after training. Overall, assertive training is effective for increasing student understanding and effective for enhancing assertive behavior.